Pengaruh Self Efficacy (Efikasi Diri) Dan Beban Kerja Terhadap Kinerja Karyawan Melalui Kepuasan Kerja Sebagai Variabel Intervening Pada PT. Victory Interational Future Cabang Mataram - Nia Rohmani; Lalu Mimbar; Topan Siswanto (Kredibel: Jurnal Ilmiah Manajemen, 2025)
The purpose of this study is to examine several things, namely : (1) the effect of self-efficacy (self-efficacy) and workload partially to job satisfaction through satisfaction, (2) the effect of self-efficacy, workload, and job satisfaction partially to employee performance, (3) the effect of self-efficacy and workload to employee performance through job satisfaction, (4) the effect of self-efficacy and workload simultaneously tehadap job satisfaction, (5) ) the effect of self-efficacy, workload and job satisfaction simultaneously tehadap employee performance. In this study using the type of associative research with a population and a sample of 38 employees at PT. Victory International Future Mataram Branch data collection techniques used in this study in the form of a questionnaire-shaped statement. The results of this study showed that: (1) self efficacy and workload have a positive and significant effect on job satisfaction because the calculated t value is higher than T table 2.714 > 1.685 and produces a significance level of T is 0.000 < 0.05 and T table 4.871 > 1.685 and produces a significance level of T is 0.000 < 0.05. (2) self efficacy, workload, and job satisfaction beinfluence positive partially significant to employee performance because the value of t calculate self efficacy is higher than T table 7.936 > 1.685 and produce significance level t is 0.010 < 0.05, t calculate workload 4.197 > 1.685 and produce significance level t is 0.00 < 0.05, and job satisfaction 11.061 > 1.685 and produce significance level 0.05 0.00 < 0.05. (3) self efficacy and workload significantly affect employee performance through job satisfaction due to sobel test self efficacy t table value 1,685 > 2,164 and workload 1,685 > 3,637. (4) self-efficacy and workload have a positive and significant effect simultaneously on job satisfaction because the results of F count 43,474 and the significance value of 0,000 < 0.05. (5) self efficacy, workload significant effect simultaneously terhadao employee performance because the value of F count 439.179 and the value of significance 0.000 < 0.05.